2004
DOI: 10.1101/gad.1167804
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ signaling exacerbates mammary gland tumor development

Abstract: Breast cancer cell lines that express the nuclear peroxisome proliferator-activated receptor ␥ (PPAR␥) can be prompted to undergo growth arrest and differentiation when treated with synthetic PPAR␥ ligands. To evaluate the therapeutic potential of increased PPAR␥ signaling in vivo, we generated transgenic mice that express a constitutively active form of PPAR␥ in mammary gland. These mice are indistinguishable from their wild-type littermates. However, when bred to a transgenic strain prone to mammary gland ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 63 publications
5
148
3
1
Order By: Relevance
“…Intriguingly, the same study also showed that overproduction of a constitutively active Vp16/PPAR␥ fusion transcription factor in mouse mammary epithelial cells exacerbates PyMT-induced tumorigenesis (51). Although Vp16/PPAR␥ overexpression may significantly alter the balance of cellular concentrations of coactivators and corepressors available for other transcriptional regulators, this study suggests that the mechanisms by which PPAR␥ regulates mammary gland tumorigenesis are extremely complex.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Intriguingly, the same study also showed that overproduction of a constitutively active Vp16/PPAR␥ fusion transcription factor in mouse mammary epithelial cells exacerbates PyMT-induced tumorigenesis (51). Although Vp16/PPAR␥ overexpression may significantly alter the balance of cellular concentrations of coactivators and corepressors available for other transcriptional regulators, this study suggests that the mechanisms by which PPAR␥ regulates mammary gland tumorigenesis are extremely complex.…”
Section: Discussionmentioning
confidence: 86%
“…Third, another study with similar breeding strategy in our laboratory showed a comparable mammary gland tumorigenesis in steroid receptor coactivator-1 Ϫ/Ϫ /PyMT and WT/ PyMT mice (data not shown). Fourth, PPAR␥ ϩ/Ϫ /PyMT and WT/ PyMT mice, generated by crossing mice with C57BL/129SvJ and FVB strain background, also showed no difference in mammary gland tumorigenesis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Since PPARγ ligands induce apoptosis in many cancers [17][18][19] and PGC-1α powerfully coactivates PPARγ [8], we asked whether PGC-1α-induced apoptosis in Ho-8910 cells is mediated by a PPARγ-dependent pathway.…”
Section: Pparγ Antagonist Suppresses Pgc-1α-induced Apoptosis In Ho-8mentioning
confidence: 99%
“…PPARγ, a member of the nuclear receptor superfamily, forms a complex with coactivator PGCs to npg regulate gene expression [8,15,16]. PPARγ has a tumorigenic role in many kinds of cancers such as colon cancer [17,18] and mammary gland cancer [19], and activation of PPARγ signaling exacerbates the development of these tumors. On the other hand, PPARγ ligands have antiproliferative activity and induce apoptosis in many cancers [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear how the functions of ␤-catenin, RXR-␣, and PPAR-␥ are connected. Indeed, some transgenic mice that express constitutively active PPAR-␥ have accelerated mammary gland tumors, compared with control animals from the same strains (40).…”
mentioning
confidence: 99%